Islamic Communication Ethics In Generation Z Parenting Patterns And Their Implications For Children's Character - Azwar, Muhammad; Rubino (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2026)
The family is a primary social institution that plays a crucial role in shaping children's character through everyday communication. In the digital age, Generation Z parents face unique challenges in maintaining ethical communication while adapting to rapid technological developments. This study examines Islamic communication ethics in the parenting patterns of Generation Z parents and their implications for children's character development in the digital age. This study used a descriptive qualitative approach, collecting data through in-depth interviews with eight Generation Z parents and analyzing them thematically. The results indicate that parents understand Islamic communication ethics as polite, gentle, dialogical, and compassionate communication implemented through persuasive interactions and role models. Despite facing challenges of gadget dominance and emotional control, Islamic communication ethics contribute positively to children's honesty, empathy, discipline, emotional control, and self-confidence.